2008
DOI: 10.1080/09546630801974912
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis caused by Fusarium sp in Sri Lanka: Prevalence, clinical features and response to itraconazole pulse therapy in six cases

Abstract: Our data reconfirmed that Fusarium nail infections are difficult to eradicate. Since the therapeutic reservoir in toenails is 11 months, these patients should be followed up for a total of 12 months before coming to the final conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
3
16
0
5
Order By: Relevance
“…in our region is higher than in other countries. Colombia, the United States, and Sri Lanka have reported rates of 6, 6.9, and 6.25 %, respectively [1,14,15]. Moreover, all patients who were diagnosed with onychomycosis caused by Fusarium spp.…”
Section: Resultsmentioning
confidence: 99%
“…in our region is higher than in other countries. Colombia, the United States, and Sri Lanka have reported rates of 6, 6.9, and 6.25 %, respectively [1,14,15]. Moreover, all patients who were diagnosed with onychomycosis caused by Fusarium spp.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that itraconazole pulse therapy is effective on Fusarium onychomycosis, showing clinical cure in 40–88% of cases . In the study conducted by Ranawaka et al . on six cases of Fusarium onychomycosis, oral itraconazole pulse therapy showed 60% clinical cure at 12 months follow‐up, and the mycological cure was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Reports from different parts of the world including India, Sri Lanka, Brazil and Argentina have also described nondermatophytes filamentous fungi as an important cause of onychomycosis. [15][16][17][18] Among non dermatophytes Alternaria alternata, Aspergillus glaucus, Aspergillus tereus and Fusarium species were the predominant isolates in our setup. Ulocladium chartarum, Scedosporium apiospermum, Scedosporium prolificans and Cladophialophora carrionii were also isolated from a few cases highlighting the role in superficial infections.…”
Section: Discussionmentioning
confidence: 99%